Laminated film
Patent Information
- Application Number
- CN202580023119.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-02-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0021]根据(6)的发明,能够使折回部侧部分的高度稳定,进一步减小蓄电体与传热部件之间的接触面的凹凸。
Smart Images

Figure CN122996545A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a laminated film. Background Technology
[0002] In recent years, research and development of secondary batteries that help improve energy efficiency have been underway to ensure that more people have access to affordable, reliable, sustainable and advanced energy.
[0003] As an outer casing for housing a secondary battery, examples include laminates having at least a metal layer and a resin layer (e.g., Patent Document 1).
[0004] [Existing technical documents] [Patent Literature]
[0005] Patent Document 1: Japanese Patent Publication No. 2022-126645 Summary of the Invention
[0006] [The technical problem that the invention aims to solve]
[0007] As secondary batteries, solid-state batteries, such as lithium metal batteries and lithium-ion secondary batteries, are known to have a solid electrolyte layer disposed between the positive and negative electrode layers. Compared with secondary batteries that use electrolytes, solid-state batteries have the advantage of a wider operating temperature range. Therefore, when a laminate is used as the outer casing of a solid-state battery, it is preferable that the outer casing itself has high heat dissipation properties.
[0008] The present invention was made in view of the above circumstances, and its object is to provide a laminated film that is used as an outer casing of a solid-state battery and can achieve excellent heat dissipation.
[0009] [Technical solutions used to solve technical problems]
[0010] (1) A laminated film used as an outer casing of a solid-state battery, wherein the laminated film has at least a metal layer and an inner resin layer, the metal layer having a thickness of more than twice that of the inner resin layer.
[0011] According to the invention of (1), it is possible to provide a laminated film with excellent heat dissipation properties.
[0012] (2) The laminated film according to (1), wherein the metal layer has a thickness of more than 2.5 times that of the inner resin layer.
[0013] According to the invention of (2), it is possible to provide a laminated film with better heat dissipation properties.
[0014] (3) A laminated film used as an outer casing of a solid-state battery, wherein the laminated film has at least a metal layer, an inner resin layer and an outer resin layer, and the thickness of the metal layer is more than 65% of the overall thickness of the laminated film.
[0015] According to the invention of (3), it is possible to provide a laminated film with better heat dissipation properties.
[0016] (4) The laminate according to (3), wherein the thickness of the metal layer is more than 70% of the overall thickness of the laminate.
[0017] According to the invention of (4), it is possible to provide a laminated film with better heat dissipation properties.
[0018] (5) The laminated film according to any one of (1) to (4), wherein the laminated film includes a receiving portion for receiving an electrode stack and a peripheral portion surrounding the receiving portion, a sealing portion disposed on the peripheral portion, the sealing portion being disposed approximately at the center of the electrode stack in the stacking direction, the sealing portion having a folded-back portion including a first region and a second region, wherein the first region extends along one side of the stacking direction of the electrode stack; the second region extends from the end of the first region on one side to the opposite side.
[0019] According to the invention of (5), the portion on the folded-back side forms multiple regions by folding back, thereby easily reducing the unevenness of the contact surface between the battery and the heat transfer component. Therefore, since gaps are less likely to occur between the secondary battery and the heat transfer component, the battery and the heat transfer component can make closer contact, thus enabling the heat of the secondary battery to be effectively transferred to the cooling and heating element.
[0020] (6) The laminated film according to (5) further has a third region that extends from the end of the second region on the other side toward the folded portion.
[0021] According to the invention of (6), the height of the folded-back side portion can be stabilized, further reducing the unevenness of the contact surface between the energy storage body and the heat transfer component. Attached Figure Description
[0022] Figure 1 This is a schematic diagram showing the configuration of a solid-state battery including the laminated film involved in the embodiments of the present invention.
[0023] Figure 2 This is a graph showing the relationship between the thickness of the metal layer and the temperature of a single cell in the embodiments of the present invention.
[0024] Figure 3This is a graph showing the relationship between the thickness of the inner resin layer and the temperature of a single cell in the embodiments of the present invention.
[0025] Figure 4 This is a graph showing the tensile strength and T-peel test results of the laminated film involved in the embodiments of the present invention. Detailed Implementation
[0026] like Figure 1 As shown, the laminated film 20 involved in this embodiment is used as the outer casing of the solid-state battery 1. The solid-state battery 1 has an electrode laminate 10 and a laminated film 20. The solid-state batteries 1 are used in a modular manner in multiple ways. A cushioning material 3 is disposed at the end of the solid-state battery 1. The solid-state battery 1 is placed on a binding bar V. A water jacket 4, which serves as a cooling device, is disposed at the lower part of the binding bar V. The cushioning material 3, the binding bar V, and the water jacket 4 are examples of battery module components comprising multiple solid-state batteries 1. Figure 1 This diagram schematically illustrates a portion of the components of the solid-state battery 1 and the battery module, and does not faithfully depict the shape and size of each component. That is, the shape and size of each component are not limited to... Figure 1 The composition can be modified without reducing the effectiveness of the present invention.
[0027] (Electrode stack) The electrode stack 10 is the power generation element of the solid-state battery 1. The electrode stack 10 has a structure in which positive and negative electrode layers are alternately stacked, separated by a solid electrolyte layer. The number of layers in each stack is not particularly limited. The solid-state battery 1 having the electrode stack 10 is not particularly limited; it can be a lithium-ion solid-state secondary battery or a lithium metal solid-state secondary battery. The operating temperature range of the solid-state battery 1 is not particularly limited; for example, it can be -40℃ to 100℃. Compared to secondary batteries using electrolytes, the solid-state battery 1 has a higher upper limit to its operating temperature range, therefore, improving heat dissipation is important when the temperature of the solid-state battery 1 rises. Especially when the size of the solid-state battery 1 is large, temperature differences are easily generated within the solid-state battery 1, making improved heat dissipation even more important. The size of the solid-state battery 1 is not particularly limited; for example, it can be 4×50×50mm or larger, or 15×100×500mm or larger.
[0028] The negative electrode layer comprises a negative electrode active material layer and a negative electrode current collector layer. The negative electrode active material layer is not particularly limited and can be composed of any material suitable for use as a negative electrode active material in solid-state batteries. As a negative electrode active material, the negative electrode active material layer can contain silicon-based active materials such as lithium metal, lithium alloys, Si, and Si alloys, or lithium titanate (Li4Ti5O4). 12The negative electrode active material layer can contain lithium transition metal oxides such as TiO2, Nb2O3, and WO3, metal sulfides, metal nitrides, carbon materials such as graphite, soft carbon, and hard carbon, and indium. In addition to the negative electrode active material, the negative electrode active material layer can also contain solid electrolytes, conductive additives, binders, and other materials that can be used in solid-state batteries. The negative electrode current collector layer is not particularly limited and can be made of copper, nickel, or stainless steel.
[0029] The solid electrolyte layer is disposed between the negative electrode layer and the positive electrode layer. There are no particular limitations on the solid electrolyte material constituting the solid electrolyte layer; any material suitable for use as an electrolyte in a solid-state battery can be used. Examples include sulfide solid electrolyte materials, oxide solid electrolyte materials, halide solid electrolytes, inorganic solid electrolytes containing lithium salts, and polymer-based solid electrolytes such as polyethylene oxide.
[0030] The positive electrode layer comprises a positive electrode active material layer and a positive electrode current collector layer. The positive electrode active material layer is not particularly limited and can be composed of any material suitable for use as a positive electrode active material in solid-state batteries. Examples of positive electrode active materials constituting the positive electrode active material layer include: LiCoO2, LiNiO2, and LiCo. x Ni y Mn z Layered positive electrode active material particles such as O2 (x+y+z=1), LiVO2, and LiCrO2; LiMn2O4, Li(Ni) 0.25 Mn 0.75 Spinel-type positive electrode active materials such as Li₂O₄, LiCoMnO₄, and Li₂NiMn₃O₈; olivine-type positive electrode active materials such as LiCoPO₄, LiMnPO₄, and LiFePO₄; solid solution oxides (Li₂MnO₃-LiMO₂ (M=Co, Ni, etc.)); conductive polymers such as polyaniline and polypyrrole; sulfides such as Li₂S, CuS, Li-Cu-S compounds, TiS₂, FeS, MoS₂, and Li-Mo-S compounds; and mixtures of sulfur and carbon, etc. The positive electrode active material can be one of the above materials or composed of two or more of the above materials. In addition to the positive electrode active material, the positive electrode layer can also contain materials that can be used as solid-state batteries, such as solid electrolytes, conductive additives, and binders. The positive electrode current collector layer is not particularly limited and can be composed of, for example, aluminum, stainless steel, or conductive carbon (graphite, carbon nanotubes, etc.).
[0031] In addition to the above, the electrode stack 10 may also have any type of layer. For example, an intermediate layer may be present between the negative electrode layer and the solid electrolyte layer. The intermediate layer has the function of suppressing dendrite formation and stabilizing the interface between the negative electrode layer and the solid electrolyte layer. The intermediate layer is composed of metals such as tin, amorphous carbon, etc.
[0032] (Laminated film) like Figure 1 As shown, the laminate 20 has at least an inner resin layer 21 and a metal layer 22. In this embodiment, the laminate 20 also has an outer resin layer 23 and an outer resin layer 24. Figure 1 The layer composition of the laminate 20 in direction D is schematically shown. Direction D is the direction along the surface on which the electrode laminate 10 is placed. Figure 1 The layer structure of the laminate 20 below the electrode stack 10 is omitted and is only generally indicated by reference numeral 20, but the layer structure of this part is the same as the layer structure in direction D.
[0033] The inner resin layer 21 is the innermost layer in the laminate 20, disposed on the electrode laminate 10 side. The inner resin layer 21 is, for example, made of a heat-welding resin. For example, the electrode laminate 10 can be encapsulated by forming the laminate 20 into a bag or tube shape, and the electrode laminate 10 can be sealed by heat-sealing the inner resin layers 21 together. Examples of resins constituting the inner resin layer 21 include polypropylene, low-density polyethylene, high-density polyethylene, polystyrene, polyvinyl chloride, AS resin, and ABS resin.
[0034] The thickness of the inner resin layer 21 is not particularly limited, but is preferably 35 μm or less, for example. Furthermore, from the viewpoint of ensuring sealing strength and insulation, it is more preferably 23 μm or more. By reducing the thickness of the inner resin layer 21 within a range that provides excellent insulation and sealing properties as the outer casing of the solid-state battery 1, the energy density of the solid-state battery 1 can be improved.
[0035] The outer resin layers 23 and 24 are disposed at the outermost side of the laminate 20. In this embodiment, the outer resin layers are described as two layers, outer resin layers 23 and 24, but the number of outer resin layers is not particularly limited, and it can also be a single layer. Since the number of adhesive layers described later can be reduced by making the outer resin layers a single layer, the energy density of the solid-state battery 1 can be improved. The resin constituting the outer resin layers 23 and 24 is not particularly limited as long as it has heat resistance to the extent that it does not melt and cause defects during heat sealing. Examples of the above-mentioned resins include polyethylene terephthalate, polyvinyl chloride, polyvinyl alcohol, polyvinylidene chloride, polyamide, polybutylene terephthalate, polyphenylene sulfide, etc. The outer resin layer is preferably composed of polyethylene terephthalate.
[0036] An adhesive layer may also be provided in the laminate 20 to improve the adhesion between the outer resin layers 23 and 24, or to improve the adhesion between the outer resin layer 23 and the metal layer 22 disposed on the metal layer 22 side. In this embodiment, an adhesive layer a1 is provided between the metal layer 22 and the outer resin layer 23, and an adhesive layer a2 is provided between the outer resin layer 23 and the outer resin layer 24. There are no particular limitations on adhesive layers a1 and a2; any adhesive layer composed of a laminating adhesive or the like can be used. Furthermore, an adhesive layer (not shown) may also be provided between the inner resin layer 21 and the metal layer 22.
[0037] The metal layer 22 is disposed on the outer side of the solid-state battery 1, closer to the inner resin layer 21. Examples of metals constituting the metal layer 22 include aluminum (Al) and stainless steel (SUS). Aluminum (Al) is preferred. In this embodiment, the metal layer 22 is disposed between the inner resin layer 21 and the outer resin layer 23. The laminate 20 of this embodiment achieves excellent heat dissipation by making the thickness of the metal layer 22 thicker than in the prior art. That is, heat is easily dissipated from the electrode laminate 10 to the outside through the metal layer 22. Figure 1 As shown, the heat generated by the electrode stack 10 is dissipated to the outside (cooling device) via the transfer path R1. Alternatively, the heat generated by the electrode stack 10 is dissipated to the outside (cooling device) via transfer paths R21 and R22. Furthermore, Figure 1 The heat transfer paths R1, R21, and R22 schematically represent the directions of heat transfer. Because the metal layer 22 is thicker than in the prior art, the heat generated by the electrode stack 10 is particularly easily dissipated to the outside via the heat transfer paths R21 and R22.
[0038] The thickness of the metal layer 22 is at least twice the thickness of the inner resin layer 21. Preferably, the thickness of the metal layer 22 is at least 2.5 times the thickness of the inner resin layer 21. Furthermore, the thickness of the metal layer is preferably at least 65% of the total thickness of the laminate 20 including the outer resin layer, and more preferably at least 70%. This provides excellent heat dissipation for the laminate 20. The absolute value of the thickness of the metal layer 22 is not particularly limited, but is preferably at least 80 μm.
[0039] The overall thickness of the laminate 20, including all the above layers, is preferably 120 μm or less. Accordingly, since the volume of the laminate 20 can be reduced, the energy density of the solid-state battery 1 and the battery module comprising multiple solid-state batteries 1 can be increased. Alternatively, increasing the thickness of the buffer material 3 improves the absorption of single-cell expansion, thereby increasing the strength of the battery module.
[0040] The laminated film described in the above embodiments includes, for example, a receiving portion for housing an electrode stack and a peripheral portion surrounding the receiving portion. A sealing portion is provided at the peripheral portion. The sealing portion is formed by bonding the laminated films together by means of adhesion or welding.
[0041] Preferably, the sealing portion has a fold-back portion, including a first region and a second region, wherein the first region extends along one side of the stacking direction of the electrode laminate; and the second region extends from one end of the first region to the opposite side. Additionally, preferably, it also has a third region that extends from the other end of the second region to one side of the fold-back portion.
[0042] According to the above configuration, since the portion of the peripheral portion adjacent to the folded-back portion, which is closer to the folded-back portion on the side of the receiving portion, is folded back along that side, the outer casing easily becomes flat at that folded-back portion. Therefore, when this portion comes into contact with the heat transfer component, the contact area can be further increased. Thus, the heat from the secondary battery can be effectively transferred to the outside, such as the cooling and heating elements.
[0043] Furthermore, according to the above structure, since the portion on the folded-back side forms multiple regions through folding, it is easier to reduce the unevenness of the contact surface between the secondary battery and the heat transfer component. Therefore, gaps are less likely to occur between the secondary battery and the heat transfer component, making it easier for them to make close contact. This allows for efficient transfer of heat from the secondary battery to external components such as cooling and heating elements. Additionally, the presence of a third region stabilizes the height of the folded-back side portion, further reducing the unevenness of the contact surface between the secondary battery and the heat transfer component.
[0044] The preferred embodiments of the present invention have been described above, but the present invention is not limited to the above embodiments, and appropriate modifications can be made within the scope of not impairing the effects of the present invention.
[0045] The present invention will now be described in more detail through embodiments. The present invention is not limited to the contents of the following embodiments.
[0046] [Example]
[0047] [Relationship between metal layer thickness and solid-state battery cell temperature] The laminate 20 is constructed as follows: The inner resin layer 21 uses PP (polypropylene) with a thickness of 80 μm; the metal layer 22 uses Al (aluminum); the outer resin layer 23 uses PA (polyamide) with a thickness of 15 μm; and the outer resin layer 24 uses PET (polyethylene terephthalate) with a thickness of 12 μm. Adhesive layers are provided between the metal layer 22 and the outer resin layer 23, and between the outer resin layer 23 and the outer resin layer 24. (The reference numerals for each component are not provided in the accompanying drawings.) Figure 1 The same applies below.
[0048] In the aforementioned laminate 20, laminates were fabricated in which the thickness of the metal layer 22 varied to 40 μm, 60 μm, and 80 μm, respectively. The heater (50 × 50 × 4 mm) of the simulated electrode stack 10 was housed within the laminate 20 and sealed. The temperature of the heater was kept constant at a heat output of 3 W, and measurements were taken. Figure 1 The temperature at measurement point M. The relationship between the thickness of metal layer 22 and the measured temperature is as follows: Figure 2 As shown in the chart.
[0049] Figure 2 The vertical axis of the graph is plotted with the temperature difference relative to the specified temperature T as the temperature (°C) of the measuring point M. Figure 2 The horizontal axis of the graph represents the thickness (μm) of Al (aluminum) as metal layer 22. For example... Figure 2 As shown, since the temperature at the measuring point M decreases with increasing the thickness of Al (aluminum) as the metal layer 22, the result is clear: the heat generated by the electrode stack 10 is more easily dissipated to the outside. Furthermore, the same experiment was conducted with a heater size of 16.2 mm × 106 mm × 520 mm, and the result was that the temperature at the measuring point M decreased by approximately 3.65 °C when the thickness of Al (aluminum) was increased from 40 μm to 80 μm.
[0050] [Relationship between the thickness of the inner resin layer and the temperature of the solid-state battery cell] The laminate 20 is constructed as follows: PP (polypropylene) is used as the inner resin layer 21, and Al (aluminum) with a thickness of 80 μm is used as the metal layer 22. In the above-described laminate 20, laminates are fabricated with the thickness of the inner resin layer 21 varying to 80 μm, 35 μm, and 23 μm, respectively. Other configurations are as described above. Figure 2 The composition is the same as in [the previous text]. [The following is a separate, unrelated sentence:] Will be with [the previous text] Figure 2 The same heater is housed in the aforementioned laminate 20 and sealed, in conjunction with Figure 2 Measurement under the same conditions Figure 1 The temperature at temperature measurement point M. The relationship between the thickness of the inner resin layer 21 and the measured temperature is as follows: Figure 3 As shown in the chart.
[0051] Figure 3 The vertical axis of the graph is plotted with the temperature difference relative to the specified temperature T1 as the temperature (°C) of the measuring point M. Figure 3 The horizontal axis of the graph represents the thickness (μm) of the PP (polypropylene) layer 21, which forms the inner resin layer. For example... Figure 3As shown, since the temperature at the temperature measuring point M decreases due to the reduction in the thickness of the PP (polypropylene) that serves as the inner resin layer 21, the result is clear: the heat generated by the electrode stack 10 is more easily dissipated to the outside.
[0052] [Insulation Test] The laminate 20 is constructed as follows: The inner resin layer 21 uses PP (polypropylene) with a thickness of 23 μm; the metal layer 22 uses Al (aluminum) with a thickness of 80 μm; and the outer resin layer uses PET (polyethylene terephthalate) with a thickness of 6 μm (making the outer resin layer a single layer). An adhesive layer is provided between the metal layer 22 and the outer resin layer. The insulation resistance value of the laminate 20 under a 1000V application was measured. Measurements were performed on the surface of the outer resin layer and the surface of the inner resin layer 21, with N=2. The insulation resistance values of the outer resin layer surface were 12.7 GΩ and 73.4 GΩ, and the insulation resistance values of the inner resin layer surface were 25.0 GΩ and 45.5 GΩ. With a judgment standard of 100 MΩ or higher, it can be confirmed that excellent insulation properties can be obtained through the laminate 20.
[0053] [Sealing test (tensile strength and T-peel test)] Tensile and T-peel tests were conducted using the laminate 20 used in the insulation tests described above. The tensile strength of a single laminate and the T-peel strength of the bonded portion after partial overlap and bonding of two laminates were measured. Both the tensile strength test and the T-peel test (sealing strength test) were performed under the following conditions: sample size: 15 mm × 10 cm, tensile speed: 100 mm / min, number of tests: 3. Furthermore, the tests were conducted under several different temperature conditions. The results are as follows: Figure 4 As shown in the chart.
[0054] Figure 4 The vertical axis of the chart represents the tensile strength of a single laminate and the T-peel strength of the bond (both in N / 15mm). Figure 4 The horizontal axis of the chart represents the temperature (°C) at the time of measurement. For example... Figure 4 As shown, under any condition, the judgment benchmark (0.3 MPa) is above, confirming that excellent sealing performance and strength can be obtained through the above-mentioned laminate 20.
[0055] [Explanation of reference numerals in the attached figures]
[0056] 1: Solid-state battery; 20: Laminated film; 21: Inner resin layer; 22: Metal layer; 23, 24: Outer resin layer.
Claims
1. A laminated film used as an outer casing for a solid-state battery, characterized in that, The laminated film has at least a metal layer and an inner resin layer. The metal layer has a thickness of more than twice that of the inner resin layer.
2. The laminated film according to claim 1, characterized in that, The metal layer has a thickness of more than 2.5 times that of the inner resin layer.
3. A laminated film used as an outer casing for a solid-state battery, characterized in that, The laminated film has at least a metal layer, an inner resin layer, and an outer resin layer. The thickness of the metal layer is more than 65% of the overall thickness of the laminate.
4. The laminated film according to claim 3, characterized in that, The thickness of the metal layer is more than 70% of the overall thickness of the laminate.
5. The laminated film according to claim 1, characterized in that, The laminated film includes a receiving portion for housing the electrode stack and a peripheral portion surrounding the receiving portion. The sealing part is disposed on the peripheral part. The sealing portion is disposed approximately at the center of the electrode laminate in the lamination direction. The sealing portion has a folded-back portion, including a first region and a second region, wherein the first region extends along one side of the stacking direction of the electrode stack; and the second region extends from the end of the first region on one side to the opposite side.
6. The laminated film according to claim 5, characterized in that, It also has a third region that extends from the end of the second region on the other side toward the folded-back portion.
Citation Information
Patent Citations
Battery packaging materials and batteries
JP2022126645A